Side-effects of laser weeding: quantifying off-target risks to earthworms (Enchytraeids) and insects (Tenebrio molitor and Adalia bipunctata) - Andreasen, Christian; Vlassi, Eleni; Johannsen, Kenneth S.; Jensen, Signe M. (Frontiers in Agronomy, 2023)
With challenges posed by chemical and mechanical conventional weed control, there are now several research and commercial projects underway to develop autonomous vehicles equipped with lasers to control weeds in field crops. Recognition systems based on artificial intelligence have been developed to locate and identify small weed seedlings, and mirrors can direct a laser beam towards the target to kill the weed with heat. Unlike chemical and mechanical weed control, Laser weeding seems to be a promising tool to replace or supplement herbicides and mechanical control, with only exposes a small treatment area of the field for the treatment. Laser weeding in contrast to other weed control measures. Unlike herbicide spraying, laser weeding leaves no chemicals in the field that may harm non-target organisms after the treatment or does not move the soil which may harm crop roots and nontarget organisms. Yet, it is well-known that laser beams can harm living organisms; the effect on the environment and fauna should be studied before laser weeding becomes a common practice. This project aimed to study the effect of laser on some living non-target organisms. We investigated the effect of laser treatment on the mortality of two species of earthworms (Enchytraeus albidus and Enchytraeus crypticus), larvae, pupas, and beetles of yellow mealworm beetles (Tenebrio molitor) and the two-spotted lady beetle (Adalia bipunctata) for increasing dosages of laser energy. In all earthworms experiments except one, the mortality rates of the worms living in the uppermost soil layer of clay, sandy, and organic soil exposed to laser heating were not significantly different from the controls even with laser dosages up to 236 J mm -2. Earthworms were in most experiments not affected at dosages appropriate for weed control. Laser doses sufficient to kill plants were lethal to the insects, and lower doses that did not kill plants killed or harmed the insects across all life stages tested. The insects were significantly harmed even when they were exposed to tiny dosages of laser. Laser weeding is a new technology and not yet widely practiced or commercialized.